2017
DOI: 10.1155/2017/4727942
|View full text |Cite
|
Sign up to set email alerts
|

Differentially Expressed MicroRNAs in the Development of Early Diabetic Retinopathy

Abstract: The pathological mechanisms of diabetic retinopathy (DR), a leading cause of blindness in adults with diabetes mellitus, remain incompletely understood. Because microRNAs (miRNAs) represent effective DR therapeutic targets, we identified aberrantly expressed miRNAs associated with cellular dysfunction in early DR and detected their potential targets. We exposed human retinal endothelial cells (HRECs) and a cell line of retinal pigment epithelial (RPE) cells to high glucose (25 mmol/L, 1–7 days) to mimic DR pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 36 publications
3
26
0
Order By: Relevance
“…The expression levels of miR-216a-5p, -34c-5p, -410-3p , and -203a-3p are significantly up-regulated in the DM group compared with that in the control group, while miR-212-3p is down-regulated, and miR-350 shows no significant change. Additionally, in our recent study, we identified several miRNAs, both in HRECs and ARPE-19 cells, whose levels increase with time under hyperglycemia; the levels of these miRNAs also increase in the retinas of STZ-induced DM rats for 4, 6, and 8 weeks after STZ injection [ 36 ]. Amongst the identified miRNAs, miR-124-3p, miR-125b-5p, miR-135b-5p , and miR-199a-5p showed a gradually decreased expression in HRECs and RPE cells; this paralleled an increase in hyperglycemia-treatment time.…”
Section: Roles Of Mirnas In Drmentioning
confidence: 99%
“…The expression levels of miR-216a-5p, -34c-5p, -410-3p , and -203a-3p are significantly up-regulated in the DM group compared with that in the control group, while miR-212-3p is down-regulated, and miR-350 shows no significant change. Additionally, in our recent study, we identified several miRNAs, both in HRECs and ARPE-19 cells, whose levels increase with time under hyperglycemia; the levels of these miRNAs also increase in the retinas of STZ-induced DM rats for 4, 6, and 8 weeks after STZ injection [ 36 ]. Amongst the identified miRNAs, miR-124-3p, miR-125b-5p, miR-135b-5p , and miR-199a-5p showed a gradually decreased expression in HRECs and RPE cells; this paralleled an increase in hyperglycemia-treatment time.…”
Section: Roles Of Mirnas In Drmentioning
confidence: 99%
“…There was an increase in studies in recent years identifying miRNAs from human samples as DR biomarkers [ 45 – 48 ]. Since our study was a small scale study, we wanted to compare/contrast with some other studies, to see whether our pilot study brought out same candidates, or different sets.…”
Section: Discussionmentioning
confidence: 99%
“…Gong et al 32 demonstrated that miR-124/miR-125b expression decreased with DR progression in vitro and in vivo; miR-124-3p and miR-125b-5p expression gradually decreased as the exposure time to high glucose increased, and these effects occurred concomitantly with the early development of DR. The tumor suppressor miR-124 is downregulated in cancers and plays a role in regulating cell proliferation and apoptosis by targeting different genes in distinct types of cancer.…”
Section: Discussionmentioning
confidence: 99%